Ergodicity and perturbation bounds for inhomogeneous birth and death processes with additional transitions from and to the origin - Zeifman, Alexander; Korotysheva, Anna; Satin, Yacov; Korolev, Victor; Shorgin, Sergey; Razumchik, Rostislav (Zielona Góra: Uniwersytet Zielonogórski)
Service life of many real-life systems cannot be considered infinite, and thus the systems will be eventually stopped or will break down. Some of them may be re-launched after possible maintenance under likely new initial conditions. In such systems, which are often modelled by birth and death processes, the assumption of stationarity may be too strong and performance characteristics obtained under this assumption may not make much sense. In such circumstances, time-dependent analysis is more meaningful.
Keywords: inhomogeneous birth and death processes; ergodicity bounds; perturbation bounds